Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
/- | |
Copyright (c) 2018 Kenny Lau. All rights reserved. | |
Released under Apache 2.0 license as described in the file LICENSE. | |
Authors: Kenny Lau | |
-/ | |
import data.fin.vec_notation | |
import logic.equiv.basic | |
/-! | |
# Equivalences for `fin n` | |
-/ | |
universes u | |
variables {m n : ℕ} | |
/-- Equivalence between `fin 0` and `empty`. -/ | |
def fin_zero_equiv : fin 0 ≃ empty := | |
equiv.equiv_empty _ | |
/-- Equivalence between `fin 0` and `pempty`. -/ | |
def fin_zero_equiv' : fin 0 ≃ pempty.{u} := | |
equiv.equiv_pempty _ | |
/-- Equivalence between `fin 1` and `unit`. -/ | |
def fin_one_equiv : fin 1 ≃ unit := | |
equiv.equiv_punit _ | |
/-- Equivalence between `fin 2` and `bool`. -/ | |
def fin_two_equiv : fin 2 ≃ bool := | |
{ to_fun := ![ff, tt], | |
inv_fun := λ b, cond b 1 0, | |
left_inv := fin.forall_fin_two.2 $ by simp, | |
right_inv := bool.forall_bool.2 $ by simp } | |
/-- `Π i : fin 2, α i` is equivalent to `α 0 × α 1`. See also `fin_two_arrow_equiv` for a | |
non-dependent version and `prod_equiv_pi_fin_two` for a version with inputs `α β : Type u`. -/ | |
@[simps {fully_applied := ff}] def pi_fin_two_equiv (α : fin 2 → Type u) : (Π i, α i) ≃ α 0 × α 1 := | |
{ to_fun := λ f, (f 0, f 1), | |
inv_fun := λ p, fin.cons p.1 $ fin.cons p.2 fin_zero_elim, | |
left_inv := λ f, funext $ fin.forall_fin_two.2 ⟨rfl, rfl⟩, | |
right_inv := λ ⟨x, y⟩, rfl } | |
lemma fin.preimage_apply_01_prod {α : fin 2 → Type u} (s : set (α 0)) (t : set (α 1)) : | |
(λ f : Π i, α i, (f 0, f 1)) ⁻¹' s ×ˢ t = | |
set.pi set.univ (fin.cons s $ fin.cons t fin.elim0) := | |
begin | |
ext f, | |
have : (fin.cons s (fin.cons t fin.elim0) : Π i, set (α i)) 1 = t := rfl, | |
simp [fin.forall_fin_two, this] | |
end | |
lemma fin.preimage_apply_01_prod' {α : Type u} (s t : set α) : | |
(λ f : fin 2 → α, (f 0, f 1)) ⁻¹' s ×ˢ t = set.pi set.univ ![s, t] := | |
fin.preimage_apply_01_prod s t | |
/-- A product space `α × β` is equivalent to the space `Π i : fin 2, γ i`, where | |
`γ = fin.cons α (fin.cons β fin_zero_elim)`. See also `pi_fin_two_equiv` and | |
`fin_two_arrow_equiv`. -/ | |
@[simps {fully_applied := ff }] def prod_equiv_pi_fin_two (α β : Type u) : | |
α × β ≃ Π i : fin 2, ![α, β] i := | |
(pi_fin_two_equiv (fin.cons α (fin.cons β fin_zero_elim))).symm | |
/-- The space of functions `fin 2 → α` is equivalent to `α × α`. See also `pi_fin_two_equiv` and | |
`prod_equiv_pi_fin_two`. -/ | |
@[simps { fully_applied := ff }] def fin_two_arrow_equiv (α : Type*) : (fin 2 → α) ≃ α × α := | |
{ inv_fun := λ x, ![x.1, x.2], | |
.. pi_fin_two_equiv (λ _, α) } | |
/-- `Π i : fin 2, α i` is order equivalent to `α 0 × α 1`. See also `order_iso.fin_two_arrow_equiv` | |
for a non-dependent version. -/ | |
def order_iso.pi_fin_two_iso (α : fin 2 → Type u) [Π i, preorder (α i)] : | |
(Π i, α i) ≃o α 0 × α 1 := | |
{ to_equiv := pi_fin_two_equiv α, | |
map_rel_iff' := λ f g, iff.symm fin.forall_fin_two } | |
/-- The space of functions `fin 2 → α` is order equivalent to `α × α`. See also | |
`order_iso.pi_fin_two_iso`. -/ | |
def order_iso.fin_two_arrow_iso (α : Type*) [preorder α] : (fin 2 → α) ≃o α × α := | |
{ to_equiv := fin_two_arrow_equiv α, .. order_iso.pi_fin_two_iso (λ _, α) } | |
/-- The 'identity' equivalence between `fin n` and `fin m` when `n = m`. -/ | |
def fin_congr {n m : ℕ} (h : n = m) : fin n ≃ fin m := | |
(fin.cast h).to_equiv | |
@[simp] lemma fin_congr_apply_mk {n m : ℕ} (h : n = m) (k : ℕ) (w : k < n) : | |
fin_congr h ⟨k, w⟩ = ⟨k, by { subst h, exact w }⟩ := | |
rfl | |
@[simp] lemma fin_congr_symm {n m : ℕ} (h : n = m) : | |
(fin_congr h).symm = fin_congr h.symm := rfl | |
@[simp] lemma fin_congr_apply_coe {n m : ℕ} (h : n = m) (k : fin n) : | |
(fin_congr h k : ℕ) = k := | |
by { cases k, refl, } | |
lemma fin_congr_symm_apply_coe {n m : ℕ} (h : n = m) (k : fin m) : | |
((fin_congr h).symm k : ℕ) = k := | |
by { cases k, refl, } | |
/-- An equivalence that removes `i` and maps it to `none`. | |
This is a version of `fin.pred_above` that produces `option (fin n)` instead of | |
mapping both `i.cast_succ` and `i.succ` to `i`. -/ | |
def fin_succ_equiv' {n : ℕ} (i : fin (n + 1)) : | |
fin (n + 1) ≃ option (fin n) := | |
{ to_fun := i.insert_nth none some, | |
inv_fun := λ x, x.cases_on' i (fin.succ_above i), | |
left_inv := λ x, fin.succ_above_cases i (by simp) (λ j, by simp) x, | |
right_inv := λ x, by cases x; dsimp; simp } | |
@[simp] lemma fin_succ_equiv'_at {n : ℕ} (i : fin (n + 1)) : | |
(fin_succ_equiv' i) i = none := by simp [fin_succ_equiv'] | |
@[simp] lemma fin_succ_equiv'_succ_above {n : ℕ} (i : fin (n + 1)) (j : fin n) : | |
fin_succ_equiv' i (i.succ_above j) = some j := | |
@fin.insert_nth_apply_succ_above n (λ _, option (fin n)) i _ _ _ | |
lemma fin_succ_equiv'_below {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : m.cast_succ < i) : | |
(fin_succ_equiv' i) m.cast_succ = some m := | |
by rw [← fin.succ_above_below _ _ h, fin_succ_equiv'_succ_above] | |
lemma fin_succ_equiv'_above {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : i ≤ m.cast_succ) : | |
(fin_succ_equiv' i) m.succ = some m := | |
by rw [← fin.succ_above_above _ _ h, fin_succ_equiv'_succ_above] | |
@[simp] lemma fin_succ_equiv'_symm_none {n : ℕ} (i : fin (n + 1)) : | |
(fin_succ_equiv' i).symm none = i := rfl | |
@[simp] lemma fin_succ_equiv'_symm_some {n : ℕ} (i : fin (n + 1)) (j : fin n) : | |
(fin_succ_equiv' i).symm (some j) = i.succ_above j := | |
rfl | |
lemma fin_succ_equiv'_symm_some_below {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : m.cast_succ < i) : | |
(fin_succ_equiv' i).symm (some m) = m.cast_succ := | |
fin.succ_above_below i m h | |
lemma fin_succ_equiv'_symm_some_above {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : i ≤ m.cast_succ) : | |
(fin_succ_equiv' i).symm (some m) = m.succ := | |
fin.succ_above_above i m h | |
lemma fin_succ_equiv'_symm_coe_below {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : m.cast_succ < i) : | |
(fin_succ_equiv' i).symm m = m.cast_succ := | |
fin_succ_equiv'_symm_some_below h | |
lemma fin_succ_equiv'_symm_coe_above {n : ℕ} {i : fin (n + 1)} {m : fin n} (h : i ≤ m.cast_succ) : | |
(fin_succ_equiv' i).symm m = m.succ := | |
fin_succ_equiv'_symm_some_above h | |
/-- Equivalence between `fin (n + 1)` and `option (fin n)`. | |
This is a version of `fin.pred` that produces `option (fin n)` instead of | |
requiring a proof that the input is not `0`. -/ | |
def fin_succ_equiv (n : ℕ) : fin (n + 1) ≃ option (fin n) := | |
fin_succ_equiv' 0 | |
@[simp] lemma fin_succ_equiv_zero {n : ℕ} : | |
(fin_succ_equiv n) 0 = none := | |
rfl | |
@[simp] lemma fin_succ_equiv_succ {n : ℕ} (m : fin n): | |
(fin_succ_equiv n) m.succ = some m := | |
fin_succ_equiv'_above (fin.zero_le _) | |
@[simp] lemma fin_succ_equiv_symm_none {n : ℕ} : | |
(fin_succ_equiv n).symm none = 0 := | |
fin_succ_equiv'_symm_none _ | |
@[simp] lemma fin_succ_equiv_symm_some {n : ℕ} (m : fin n) : | |
(fin_succ_equiv n).symm (some m) = m.succ := | |
congr_fun fin.succ_above_zero m | |
@[simp] lemma fin_succ_equiv_symm_coe {n : ℕ} (m : fin n) : | |
(fin_succ_equiv n).symm m = m.succ := | |
fin_succ_equiv_symm_some m | |
/-- The equiv version of `fin.pred_above_zero`. -/ | |
lemma fin_succ_equiv'_zero {n : ℕ} : | |
fin_succ_equiv' (0 : fin (n + 1)) = fin_succ_equiv n := rfl | |
/-- `equiv` between `fin (n + 1)` and `option (fin n)` sending `fin.last n` to `none` -/ | |
def fin_succ_equiv_last {n : ℕ} : fin (n + 1) ≃ option (fin n) := | |
fin_succ_equiv' (fin.last n) | |
@[simp] lemma fin_succ_equiv_last_cast_succ {n : ℕ} (i : fin n) : | |
fin_succ_equiv_last i.cast_succ = some i := | |
fin_succ_equiv'_below i.2 | |
@[simp] lemma fin_succ_equiv_last_last {n : ℕ} : | |
fin_succ_equiv_last (fin.last n) = none := | |
by simp [fin_succ_equiv_last] | |
@[simp] lemma fin_succ_equiv_last_symm_some {n : ℕ} (i : fin n) : | |
fin_succ_equiv_last.symm (some i) = i.cast_succ := | |
fin_succ_equiv'_symm_some_below i.2 | |
@[simp] lemma fin_succ_equiv_last_symm_coe {n : ℕ} (i : fin n) : | |
fin_succ_equiv_last.symm ↑i = i.cast_succ := | |
fin_succ_equiv'_symm_some_below i.2 | |
@[simp] lemma fin_succ_equiv_last_symm_none {n : ℕ} : | |
fin_succ_equiv_last.symm none = fin.last n := | |
fin_succ_equiv'_symm_none _ | |
/-- Equivalence between `Π j : fin (n + 1), α j` and `α i × Π j : fin n, α (fin.succ_above i j)`. -/ | |
@[simps { fully_applied := ff}] | |
def equiv.pi_fin_succ_above_equiv {n : ℕ} (α : fin (n + 1) → Type u) (i : fin (n + 1)) : | |
(Π j, α j) ≃ α i × (Π j, α (i.succ_above j)) := | |
{ to_fun := λ f, (f i, λ j, f (i.succ_above j)), | |
inv_fun := λ f, i.insert_nth f.1 f.2, | |
left_inv := λ f, by simp [fin.insert_nth_eq_iff], | |
right_inv := λ f, by simp } | |
/-- Order isomorphism between `Π j : fin (n + 1), α j` and | |
`α i × Π j : fin n, α (fin.succ_above i j)`. -/ | |
def order_iso.pi_fin_succ_above_iso {n : ℕ} (α : fin (n + 1) → Type u) [Π i, has_le (α i)] | |
(i : fin (n + 1)) : | |
(Π j, α j) ≃o α i × (Π j, α (i.succ_above j)) := | |
{ to_equiv := equiv.pi_fin_succ_above_equiv α i, | |
map_rel_iff' := λ f g, i.forall_iff_succ_above.symm } | |
/-- Equivalence between `fin (n + 1) → β` and `β × (fin n → β)`. -/ | |
@[simps { fully_applied := ff}] | |
def equiv.pi_fin_succ (n : ℕ) (β : Type u) : | |
(fin (n+1) → β) ≃ β × (fin n → β) := | |
equiv.pi_fin_succ_above_equiv (λ _, β) 0 | |
/-- Equivalence between `fin m ⊕ fin n` and `fin (m + n)` -/ | |
def fin_sum_fin_equiv : fin m ⊕ fin n ≃ fin (m + n) := | |
{ to_fun := sum.elim (fin.cast_add n) (fin.nat_add m), | |
inv_fun := λ i, @fin.add_cases m n (λ _, fin m ⊕ fin n) sum.inl sum.inr i, | |
left_inv := λ x, by { cases x with y y; dsimp; simp }, | |
right_inv := λ x, by refine fin.add_cases (λ i, _) (λ i, _) x; simp } | |
@[simp] lemma fin_sum_fin_equiv_apply_left (i : fin m) : | |
(fin_sum_fin_equiv (sum.inl i) : fin (m + n)) = fin.cast_add n i := rfl | |
@[simp] lemma fin_sum_fin_equiv_apply_right (i : fin n) : | |
(fin_sum_fin_equiv (sum.inr i) : fin (m + n)) = fin.nat_add m i := rfl | |
@[simp] lemma fin_sum_fin_equiv_symm_apply_cast_add (x : fin m) : | |
fin_sum_fin_equiv.symm (fin.cast_add n x) = sum.inl x := | |
fin_sum_fin_equiv.symm_apply_apply (sum.inl x) | |
@[simp] lemma fin_sum_fin_equiv_symm_apply_nat_add (x : fin n) : | |
fin_sum_fin_equiv.symm (fin.nat_add m x) = sum.inr x := | |
fin_sum_fin_equiv.symm_apply_apply (sum.inr x) | |
@[simp] lemma fin_sum_fin_equiv_symm_last : | |
fin_sum_fin_equiv.symm (fin.last n) = sum.inr 0 := | |
fin_sum_fin_equiv_symm_apply_nat_add 0 | |
/-- The equivalence between `fin (m + n)` and `fin (n + m)` which rotates by `n`. -/ | |
def fin_add_flip : fin (m + n) ≃ fin (n + m) := | |
(fin_sum_fin_equiv.symm.trans (equiv.sum_comm _ _)).trans fin_sum_fin_equiv | |
@[simp] lemma fin_add_flip_apply_cast_add (k : fin m) (n : ℕ) : | |
fin_add_flip (fin.cast_add n k) = fin.nat_add n k := | |
by simp [fin_add_flip] | |
@[simp] lemma fin_add_flip_apply_nat_add (k : fin n) (m : ℕ) : | |
fin_add_flip (fin.nat_add m k) = fin.cast_add m k := | |
by simp [fin_add_flip] | |
@[simp] lemma fin_add_flip_apply_mk_left {k : ℕ} (h : k < m) | |
(hk : k < m + n := nat.lt_add_right k m n h) | |
(hnk : n + k < n + m := add_lt_add_left h n) : | |
fin_add_flip (⟨k, hk⟩ : fin (m + n)) = ⟨n + k, hnk⟩ := | |
by convert fin_add_flip_apply_cast_add ⟨k, h⟩ n | |
@[simp] lemma fin_add_flip_apply_mk_right {k : ℕ} (h₁ : m ≤ k) (h₂ : k < m + n) : | |
fin_add_flip (⟨k, h₂⟩ : fin (m + n)) = ⟨k - m, tsub_le_self.trans_lt $ add_comm m n ▸ h₂⟩ := | |
begin | |
convert fin_add_flip_apply_nat_add ⟨k - m, (tsub_lt_iff_right h₁).2 _⟩ m, | |
{ simp [add_tsub_cancel_of_le h₁] }, | |
{ rwa add_comm } | |
end | |
/-- Rotate `fin n` one step to the right. -/ | |
def fin_rotate : Π n, equiv.perm (fin n) | |
| 0 := equiv.refl _ | |
| (n+1) := fin_add_flip.trans (fin_congr (add_comm _ _)) | |
lemma fin_rotate_of_lt {k : ℕ} (h : k < n) : | |
fin_rotate (n+1) ⟨k, lt_of_lt_of_le h (nat.le_succ _)⟩ = ⟨k + 1, nat.succ_lt_succ h⟩ := | |
begin | |
dsimp [fin_rotate], | |
simp [h, add_comm], | |
end | |
lemma fin_rotate_last' : fin_rotate (n+1) ⟨n, lt_add_one _⟩ = ⟨0, nat.zero_lt_succ _⟩ := | |
begin | |
dsimp [fin_rotate], | |
rw fin_add_flip_apply_mk_right, | |
simp, | |
end | |
lemma fin_rotate_last : fin_rotate (n+1) (fin.last _) = 0 := | |
fin_rotate_last' | |
lemma fin.snoc_eq_cons_rotate {α : Type*} (v : fin n → α) (a : α) : | |
@fin.snoc _ (λ _, α) v a = (λ i, @fin.cons _ (λ _, α) a v (fin_rotate _ i)) := | |
begin | |
ext ⟨i, h⟩, | |
by_cases h' : i < n, | |
{ rw [fin_rotate_of_lt h', fin.snoc, fin.cons, dif_pos h'], | |
refl, }, | |
{ have h'' : n = i, | |
{ simp only [not_lt] at h', exact (nat.eq_of_le_of_lt_succ h' h).symm, }, | |
subst h'', | |
rw [fin_rotate_last', fin.snoc, fin.cons, dif_neg (lt_irrefl _)], | |
refl, } | |
end | |
@[simp] lemma fin_rotate_zero : fin_rotate 0 = equiv.refl _ := rfl | |
@[simp] lemma fin_rotate_one : fin_rotate 1 = equiv.refl _ := | |
subsingleton.elim _ _ | |
@[simp] lemma fin_rotate_succ_apply {n : ℕ} (i : fin n.succ) : | |
fin_rotate n.succ i = i + 1 := | |
begin | |
cases n, | |
{ simp }, | |
rcases i.le_last.eq_or_lt with rfl|h, | |
{ simp [fin_rotate_last] }, | |
{ cases i, | |
simp only [fin.lt_iff_coe_lt_coe, fin.coe_last, fin.coe_mk] at h, | |
simp [fin_rotate_of_lt h, fin.eq_iff_veq, fin.add_def, nat.mod_eq_of_lt (nat.succ_lt_succ h)] }, | |
end | |
@[simp] lemma fin_rotate_apply_zero {n : ℕ} : fin_rotate n.succ 0 = 1 := | |
by rw [fin_rotate_succ_apply, zero_add] | |
lemma coe_fin_rotate_of_ne_last {n : ℕ} {i : fin n.succ} (h : i ≠ fin.last n) : | |
(fin_rotate n.succ i : ℕ) = i + 1 := | |
begin | |
rw fin_rotate_succ_apply, | |
have : (i : ℕ) < n := lt_of_le_of_ne (nat.succ_le_succ_iff.mp i.2) (fin.coe_injective.ne h), | |
exact fin.coe_add_one_of_lt this | |
end | |
lemma coe_fin_rotate {n : ℕ} (i : fin n.succ) : | |
(fin_rotate n.succ i : ℕ) = if i = fin.last n then 0 else i + 1 := | |
by rw [fin_rotate_succ_apply, fin.coe_add_one i] | |
/-- Equivalence between `fin m × fin n` and `fin (m * n)` -/ | |
@[simps] | |
def fin_prod_fin_equiv : fin m × fin n ≃ fin (m * n) := | |
{ to_fun := λ x, ⟨x.2 + n * x.1, | |
calc x.2.1 + n * x.1.1 + 1 | |
= x.1.1 * n + x.2.1 + 1 : by ac_refl | |
... ≤ x.1.1 * n + n : nat.add_le_add_left x.2.2 _ | |
... = (x.1.1 + 1) * n : eq.symm $ nat.succ_mul _ _ | |
... ≤ m * n : nat.mul_le_mul_right _ x.1.2⟩, | |
inv_fun := λ x, (x.div_nat, x.mod_nat), | |
left_inv := λ ⟨x, y⟩, | |
have H : 0 < n, from nat.pos_of_ne_zero $ λ H, nat.not_lt_zero y.1 $ H ▸ y.2, | |
prod.ext | |
(fin.eq_of_veq $ calc | |
(y.1 + n * x.1) / n | |
= y.1 / n + x.1 : nat.add_mul_div_left _ _ H | |
... = 0 + x.1 : by rw nat.div_eq_of_lt y.2 | |
... = x.1 : nat.zero_add x.1) | |
(fin.eq_of_veq $ calc | |
(y.1 + n * x.1) % n | |
= y.1 % n : nat.add_mul_mod_self_left _ _ _ | |
... = y.1 : nat.mod_eq_of_lt y.2), | |
right_inv := λ x, fin.eq_of_veq $ nat.mod_add_div _ _ } | |
/-- Promote a `fin n` into a larger `fin m`, as a subtype where the underlying | |
values are retained. This is the `order_iso` version of `fin.cast_le`. -/ | |
@[simps apply symm_apply] | |
def fin.cast_le_order_iso {n m : ℕ} (h : n ≤ m) : fin n ≃o {i : fin m // (i : ℕ) < n} := | |
{ to_fun := λ i, ⟨fin.cast_le h i, by simpa using i.is_lt⟩, | |
inv_fun := λ i, ⟨i, i.prop⟩, | |
left_inv := λ _, by simp, | |
right_inv := λ _, by simp, | |
map_rel_iff' := λ _ _, by simp } | |
/-- `fin 0` is a subsingleton. -/ | |
instance subsingleton_fin_zero : subsingleton (fin 0) := | |
fin_zero_equiv.subsingleton | |
/-- `fin 1` is a subsingleton. -/ | |
instance subsingleton_fin_one : subsingleton (fin 1) := | |
fin_one_equiv.subsingleton | |